2017
DOI: 10.18632/oncotarget.14413
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyllin I induces mitophagic and apoptotic cell death in human breast cancer cells by increasing mitochondrial PINK1 levels

Abstract: The molecular mechanisms underlying the anti-breast cancer effects of polyphyllin I, a natural compound extracted from Paris polyphylla rhizomes, are not fully understood. In the present study, we found that polyphyllin I induces mitochondrial translocation of DRP1 by dephosphorylating DRP1 at Ser637, leading to mitochondrial fission, cytochrome c release from mitochondria into the cytosol and, ultimately apoptosis. Polyphyllin I also increased the stabilization of full-length PINK1 at the mitochondrial surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…Our transmission electron microscope and confocal microscope assay indicated that IR‐783 increased mitochondrial fragmentation. Researchers have previously demonstrated that Drp1 effectively influences the mitochondrial fission process in cells by translocation of Drp1 to the mitochondrial outer membrane . To further confirm these results in our experiment, western blot analysis showed that treatment of cells with IR‐783 significantly increased the levels of Drp1 in mitochondria in a dose‐dependent manner, decreased the expression of mitochondria fusion regulators Mfn1 and OPA1, and increased the expression of mitochondria fission regulators MFF and Fis1 in the whole cell lysate (Figure D).…”
Section: Resultssupporting
confidence: 85%
“…Our transmission electron microscope and confocal microscope assay indicated that IR‐783 increased mitochondrial fragmentation. Researchers have previously demonstrated that Drp1 effectively influences the mitochondrial fission process in cells by translocation of Drp1 to the mitochondrial outer membrane . To further confirm these results in our experiment, western blot analysis showed that treatment of cells with IR‐783 significantly increased the levels of Drp1 in mitochondria in a dose‐dependent manner, decreased the expression of mitochondria fusion regulators Mfn1 and OPA1, and increased the expression of mitochondria fission regulators MFF and Fis1 in the whole cell lysate (Figure D).…”
Section: Resultssupporting
confidence: 85%
“…Increasing evidences has shown that natural products not only serve key roles in the detection and evolvement of novel drugs, but they may be used as molecular probes for screening treatment targets (14,15). Paris polyphyllin is a Polyphyllin I inhibits invasion and epithelial-mesenchymal transition via CIP2A/PP2A/ERK signaling in prostate cancer medicinal herb in the Shennongjia National Nature Reserve of China, which may treat fevers, headaches, burns, wounds, and exhibit immune-regulatory and antitumor abilities (16,17). Polyphyllin I (PPI), a bioactive phytochemical isolated from the rhizoma of P. polyphylla, exhibits preclinical antitumor efficacy in several cancer types, including breast, lung, gastric, and ovarian cancer, as well as osteosarcoma (16,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Paris polyphyllin is a Polyphyllin I inhibits invasion and epithelial-mesenchymal transition via CIP2A/PP2A/ERK signaling in prostate cancer medicinal herb in the Shennongjia National Nature Reserve of China, which may treat fevers, headaches, burns, wounds, and exhibit immune-regulatory and antitumor abilities (16,17). Polyphyllin I (PPI), a bioactive phytochemical isolated from the rhizoma of P. polyphylla, exhibits preclinical antitumor efficacy in several cancer types, including breast, lung, gastric, and ovarian cancer, as well as osteosarcoma (16,18,19). Recently, PPI was found to increase the sensitivity of liver cancer HepG2 cells to cisplatin, and activate autophagy via the PI3K/Akt/mTOR signaling pathway (20).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, PPI inhibited tumor growth and induced apoptosis in human breast cancer cells, and these effects were enhanced by activating the PTEN-induced kinase 1 signaling pathway [11]. PPI also demonstrated anti-tumor activity on ovarian cancer in vivo via modulation of caspase-9, c-Jun, and secreted glycoprotein Wnt5a [13].…”
Section: Introductionmentioning
confidence: 99%